Analysis of Ankle sEMG on Both Stable and Unstable Surfaces for Elderly and Young Women—A Pilot Study - Błaszczyszyn, Monika (Int J Environ Res Public Health, 2019)
Body aging is frequently accompanied with numerous consequences such as increased tendency to falls, which may be connected not only with the impaired ability of keeping balance, but also with some limitations of the system responsible for the maintenance of balance. The aim of this study was defining the importance of muscle activity in the ankle joint when standing on stable and unstable surfaces with eyes open and closed as well as examining indications of the influence of body aging on the activity of the selected muscles. The study was carried out on a group of 20 healthy women divided into two age groups (aged 24 ± 3.6 years and aged 64 ± 4.2 years). The activity of muscles stabilizing the ankle joint while standing on different types of surfaces was tested with an EMG (surface electromyography) on both elderly and young women during trials with open and closed eyes. The tests showed higher activation in the evaluated muscles of the anterior group (tibialis anterior (TA), peroneus longus (PL)) of elderly women. For the posterior shin muscles of both groups, a higher activation was observed in the gastrocnemius lateralis muscle (GL) of elderly women, whereas gastrocnemius medialis muscle (GM) showed highly comparable activity. The results obtained in this work confirm the importance of proprioception training and muscle strength in the rehabilitation of older people as well as in prophylactic exercise aimed toward the prevention of ankle injuries.